The significance of integrin ligand nanopatterning on lipid raft clustering in hematopoietic stem cells - Altrock, Eva; Muth, Christine; Spatz, Joachim P. (Biomaterials, 2012)
Hematopoietic stem cells (HSCs) are the vital, life-long source of all blood cell types. They are found in stem cell niches, specific anatomic locations that offer all the factors and signals necessary for the maintenance of the stem cell potential of HSCs. Much attention has been paid to the biochemical composition of the niches, but only little is known about the influence of physical parameters, such as ligand nanopatterns, on HSCs. To investigate the impact of nanometer-scale spacing between cell ligands on HSC adhesion, integrin distribution and signal transduction, we employed geometrically defined, nanostructured, bio-functionalized surfaces. HSCs proved to be sensitive to the lateral distance between the presented ligands with regard to adhesion and lipid raft clustering, the latter being a prerequisite for the formation of signaling complexes. Furthermore, an extensive redistribution of stem cell markers, integrins and phosphorylated proteins in HSCs was observed. In conclusion, integrin-mediated adhesion and signaling of HSCs proved to depend on the nanostructured presentation of ligands in their environment. In this work, we show that the nanostructure of the matrix is an important parameter influencing HSC behavior that should be integrated into biomaterial-based approaches aiming at HSC multiplication or differentiation.